2021
DOI: 10.3310/hta25100
|View full text |Cite
|
Sign up to set email alerts
|

Conservative treatment for uncomplicated appendicitis in children: the CONTRACT feasibility study, including feasibility RCT

Abstract: Background Although non-operative treatment is known to be effective for the treatment of uncomplicated acute appendicitis in children, randomised trial data comparing important outcomes of non-operative treatment with those of appendicectomy are lacking. Objectives The objectives were to ascertain the feasibility of conducting a multicentre randomised controlled trial comparing the clinical effectiveness and cost-effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 132 publications
0
36
0
Order By: Relevance
“…Whether a preference for non-operative treatment remains once comparative data are available remains to be seen. As with any survey, hypothetical choices made by parents may differ from the choices they may make if their child were to actually develop appendicitis, yet our observations in treating patients and through our research confirm significant interest in non-operative treatment [ 13 , 20 ]. We should also note that this work was undertaken prior to the SARS-CoV-2 pandemic, a period during which there was much greater use of non-operative treatment than had previously been the case—certainly within the UK [ 21 ].…”
Section: Discussionmentioning
confidence: 80%
“…Whether a preference for non-operative treatment remains once comparative data are available remains to be seen. As with any survey, hypothetical choices made by parents may differ from the choices they may make if their child were to actually develop appendicitis, yet our observations in treating patients and through our research confirm significant interest in non-operative treatment [ 13 , 20 ]. We should also note that this work was undertaken prior to the SARS-CoV-2 pandemic, a period during which there was much greater use of non-operative treatment than had previously been the case—certainly within the UK [ 21 ].…”
Section: Discussionmentioning
confidence: 80%
“…A total of 37 762 articles were retrieved, of which 37 710 were identified from the bibliographic databases and 52 were identified via Google and/or relevant websites. A total of 77 COS fulfilled inclusion criteria (published in 98 articles) (eFigure 1 in the Supplement).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 74 COS with complete methods reporting, only 6 (8%) met all 12 criteria for COS development (eFigure 4 and eTable 4 in the Supplement). Scope was relatively well reported, with 3 specifications for scope found in 98% or more. On the other hand, the consensus process was generally poorly reported; the scoring process (9a) was reported in 17 COS (23%) and consensus definition (9b) and criteria for including/dropping/adding outcomes (10) were reported in 16 COS (22%), 3 of which need to be described a priori.…”
Section: Resultsmentioning
confidence: 99%
“…The CONTRACT feasibility study identified key cost drivers as cost of inpatient ward stay and cost of surgery. The study included outpatient costs up to the 6 months follow-up period and evidenced a significant cost reduction in the non-operative treatment arm as compared to the appendectomy arm ( p < 0.001) [ 18 ]. In the randomized controlled study conducted by Hansson et al there was similarly a significant cost reduction associated with the antibiotic treatment group though limited to only in-hospital costs incurred [ 19 ].…”
Section: Discussionmentioning
confidence: 99%